Enthalpies of combustion, vapour pressures, and enthalpies of sublimation of the 1,5-and 1,8-diaminonaphthalenes - da Silva, MAVR (2010)
The standard (p degrees = 0.1 MPa) molar enthalpies of formation, in the crystalline state, of 1,5-diaminonaphthalene and 1,8-diaminonaphthalene were derived from the standard molar energies of combustion, in oxygen, at T = 298.15 K, measured by static-bomb combustion calorimetry. The Knudsen mass-loss effusion technique was used to measure the dependence of the vapour pressure of the solid isomers of diaminonaphthalene with the temperature, from which the standard molar enthalpies of sublimation were derived using the Clausius-Clapeyron equation. [GRAPHICS] Combining these two experimental values, the gas-phase standard molar enthalpies of formation, at T = 298.15 K, were derived and compared with those estimated using two different empirical methods of Delta fH degrees(m)(g) estimation: the Cox scheme and the Benson's Group Method. Moreover, the standard (p degrees = 0.1 MPa) molar entropies and Gibbs energies of sublimation, at T = 298.15 K, were derived for the two diaminonaphthalene isomers.